Electromagnetic interference shielding effectiveness of aluminum foams with different porosity - Xu, Zhengbin; Hao, Hai (Journal of alloys and compounds, 2014)
•The EMI shielding performance of aluminum foams with different porosity is studied.•The effectiveness remains similar firstly, then increases with increasing porosity.•The effectiveness generally decreases with increasing frequency.•The EMI shielding mechanism equation of aluminum foam is proposed innovatively.•The reflection loss and multiple reflections are dominant factors. Aluminum foams with different porosity are fabricated by varying processing parameters using melt foaming method. The macro–micro structure characteristics and electromagnetic interference (EMI) shielding effectiveness of aluminum foams are investigated. The results indicate that the pore walls mainly consist of aluminum matrix, Al4Ca phases at the grain boundary and some defects including cracks, compound particulate collections on the pore inner walls. Aluminum foams possess good EMI shielding effectiveness of 25–75dB to the space plane electromagnetic wave within the frequency of 130–1800MHz. Its EMI shielding effectiveness generally increases with increasing porosity and decreases with increasing frequency. Furthermore, the electromagnetic shielding mechanism is systematically explored and the EMI shielding equation applied to aluminum foams is also proposed, which is correlated to reflection loss, absorption loss, multiple reflections loss, eddy-current loss, wave–current interaction and any other factors. The experimental results can be well explained qualitatively.